Community Empowerment through Organic Waste Processing - Widya Prarikeslan; Desri Nora; Sri Mariya; Dion Lovani; Viki Aulia Pratama (Postgraduate, University of Mataram, 2023)
Bukittinggi is the largest wholesale trade center on the island of Sumatra. In the economic sector, Bukittinggi is the city with the second-largest GRDP in West Sumatra. The most visited tourist spot is Jam Gadang. Throughout 2020, the volume of waste in Bukittinggi City transported to the landfill in Payakumbuh was 40,424 tons, or 110.25 tons/day. This number increased compared to the volume in 2019 of 32,236 tons or 107.4 tons/day. Based on these problems, community solutions are needed. The solution offered is separating and processing organic waste into eco enzymes as a solution to reduce the accumulation of organic waste. Eco enzyme is a liquid extract produced from fermenting leftover vegetables and fruit with brown sugar as a substrate. The activity plan is carried out with the main aim of overcoming problems that occur in partner communities as previously described. This Community Partnership Program uses counseling and training methods for making Eco Enzyme from organic waste so that community groups in Pulai Anak Air Bukittinggi Village can manage organic waste into fertilizer, cleaners, etc. The activity stages begin with the preparation stage, the implementation stage, and end with the monitoring and evaluation stage. The output targets to be achieved include articles, activity videos, liquid fertilizer, cleaners, etc. which can be used by the community, especially the PKK and Pokdarwis groups in Pulai Anak Air Bukittinggi Village.